Molecular methods for the detection and identification of parasitoids within larval wheat midges - Dominique Mingeot; Sandrine Chavalle; Peter Neerup Buhl; Gontran Sonet; Benjamin Dubois; Louis Hautier (Scientific Reports)
Abstract Three species of cecidomyiid midges (Diptera: Cecidomyiidae) cause significant yield losses on wheat in Europe: Sitodiplosis mosellana (Géhin), Contarinia tritici (Kirby) and Haplodiplosis marginata (von Roser). Eggs and young larvae may be parasitised by a complex of hymenopteran parasitoids belonging to the Pteromalidae and Platygastridae families which contributes to natural pest control. We have developed molecular tools for detecting and identifying seven parasitoid species previously encountered in Belgium inside individual wheat midge larvae. Barcode DNA sequences from COI, 18S and 28S genes were obtained from the midges and parasitoid species. Each of the three genes allowed all the species to be distinguished although 18S was the only one displaying a barcoding gap, both between parasitoids and midges, and at the species level. Based on the 18S gene, we developed a TaqMan assay to assess parasitism in midge larvae, regardless of the midge and parasitoid species. Next, two group-specific PCR primer pairs were generated, allowing the separate amplification of midge DNA or parasitoid DNA in parasitised individuals and subsequent identification by Sanger sequencing. Finally, species-specific primers were designed to identify six parasitoid species by simple PCR amplification. These tools were successfully applied to assess the parasitism rate of S. mosellana larvae in seven Belgian fields.